Hydrogen-Electric Coupling Coordinated Control Strategy of Multi-Station Integrated System Based on the Honeycomb Topology - Wang, Wenyong; Huo, Qunhai; Zhang, Ningyu; Ni, Jianfu; Zhu, Jinda; Yu, Zuofei; Wei, Tongzhen (Frontiers in Energy Research, 2022)
With the high proportion accession of renewable energy and randomness of load side in new energy power system, unbalanced feeder power and heavy overload of transformer caused by massive access of highly uncertain source loads become more and more serious. In order to solve the above problems, a honeycomb topology of multi-station integrated system is proposed. Soft open point (SOP) is used as the key integrated equipment of the internal unit of multi-station integrated system. The honeycomb grid structure is composed of flexible nodes, and the multi-station integrated system is composed of multi network flexible interconnection. Based on the characteristics of regional resource endowment, hydrogen energy flow is deeply coupled in part of honeycomb grids. In order to improve the reliability and flexibility of the multi-station integrated unit, the structure of the new multi-station integrated unit, the power balance constraints on the unit and the switching process of SOP control mode is studied. At the same time, the hydrogen electricity coupling structure and the coordinated control strategy of hydrogen electricity conversion is proposed to solve the problem of deep application of hydrogen energy. Finally, the effectiveness of the proposed multi-station integrated system is verified by three simulation models.